Painful Diabetic Neuropathy in Japanese Diabetic Patients Is Common but Underrecognized. (26th November 2013) - Tsuji, Mayumi; Yasuda, Tetsuyuki; Kaneto, Hideaki; Matsuoka, Taka-aki; Hirose, Takahisa; Kawamori, Ryuzo; Iseki, Masako; Shimomura, Iichiro; Shibata, Masahiko
Abstract : Although chronic pain due to diabetic neuropathy, defined as painful diabetic neuropathy (PDN), is a debilitating and distressing complication of diabetes, epidemiological data on PDN has been scarce, especially in Asia. We evaluated the prevalence of Japanese PDN and its impact on their quality of life (QOL) and metnal state. In addition, we examined to which extent physicians are aware of patients' PDN. A total of 298 patients with diabetes were found to be eligible for the study. We revealed that substantial percentage (22.1%) of Japanese diabetic patients had PDN and that PDN had negative effect on patients' QOL and mental state. However, physicians were aware of PDN in only 36.4% of patients with the condition. To the best of our knowledge, this is the first report showing the extent of physicians' awareness of patients' PDN. In conclusion, physicians treating diabetes need to be more aware of patients' PDN in everyday clinical practice to prevent the progression of PDN and improve the patients' QOL and mental state.